Relationship Between Sensory Processing, Resilience, Attitudes and Drug use in Portuguese Adults - Borges, José Manuel; Castillo, José Antonio García del; Marzo, Juan Carlos; Castillo-López, Álvaro García del (Paidéia (Ribeirão Preto), 2017)
Research suggests that the relationship between resilience and substance use is a non-linear and multifactorial psychological process. Surprisingly, sensory processing is rarely mentioned as a variable associated with this phenomenon. In this study, we investigated the relationship between resilience, sensory processing, attitudes and consumption behaviors for alcohol, tobacco and other psychoactive substances. For this, we used four instruments: Adult / Adolescent Sensory Profile; Resilience Scale; Attitudes scales; Tobacco, Alcohol and Other Drug Use Scale. The sample consisted of 340 healthy adult participants, of whom 261 (76.8%) were women and 79 (23.2%) men. As for chronological age, the youngest person was 18 and the oldest was 76 years (M = 39; DP = 11). Sensory processing was associated with the intake behaviors and attitudes. Sensory imbalances appeared to be implicated in decreased resilience.